MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SD MELALUI PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF MENGGUNAKAN MODEL PROJECT BASED LEARNING (PJBL) TINJAUAN TAHUN 2020-2025 - Purnama Sari, Pemi; Widiarti, Nuni; Eko Handoyo; Agus Yuwono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Critical thinking skills are one of the main skills that students must have in the 21st century to be able to face problems in real life. However, in reality, students' critical thinking skills are still relatively low due to the monotonous teaching and learning process, the less than optimal use of learning media, and the learning media used are only conventional media and have not utilized technology as a learning medium that is in accordance with the development of current technological advances, so that it can actively involve students in the learning process to improve students' critical thinking skills. This study aims to examine the improvement of elementary school students' critical thinking skills through the development of interactive learning media using the project based learning (PJBL) learning model. The research method used is a literature study of journal articles related to interactive learning media, project based learning (PJBL) learning models and critical thinking skills. The data analysis technique used is qualitative analysis. The results of the study show that interactive learning media using the project based learning (PJBL) model is effective in improving elementary school students' critical thinking skills.